Do Robo-Advisors As Moderating Variables Weaken The Overconfidence and Loss Aversion Behavior Bias of Young Investors’ Mutual Fund Investment Decisions? - Liliana Inggrit Wijaya; Victor Marcelino Liangga; Bertha Silvia Sutejo (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Behavioral bias factors influence individual decision-making. Technological innovations in the financial services industry have introduced automated financial advisors, or robo-advisors, to assist in mutual fund investment decisions and reduce behavioral biases. Purpose: This study aims to prove the influence of overconfidence and loss aversion behavior bias on mutual fund investment decisions by using robo-advisors as moderator variables.Design/methodology/approach: The research sample was 100 respondents with the criteria of young investors in the age range of 18 to 25 who invested in mutual funds for the last five years and were officially registered with the Financial Services Authority. The data processing method uses multiple linear analysis with moderation dummy variable, using a robo-advisor or not.Finding/Result: The results indicate that overconfidence and loss aversion biases significantly impact mutual fund investment decisions positively. Apart from that, the results also show that robo-advisors succeed in weakening the relationship between overconfidence bias and mutual fund investment decisions. Meanwhile, robo-advisors show results that cannot moderate the relationship between loss aversion and mutual fund investment decisions.Conclusion: Robo-advisors moderate the relationship between overconfidence bias and investment decisions but do not moderate the relationship between loss aversion and mutual fund investment decisions. The high overconfidence is caused by the ease of access to information related to investment assets that is widely spread through social media. Young investors are expected to be able to screen all information related to investment knowledge to reduce loss aversion from young investors. It can help investors make more rational decisions.Originality/value (State of the art):This research is unique because it examines the behavioral biases associated with robo-advisors on investment decisions, especially investments in mutual funds. This research is novel and includes artificial intelligence technology developing in finance using robo-advisor and mutual fund investment. These have managerial implications, such as the high overconfidence in the younger generation due to easy access to information related to investment assets, which is widely spread via social media. Knowledge related to finance is considered capable of reducing loss aversion from young investors to help them make more rational and better decisions. Robo-advisor technology has reduced the irrationality of mutual fund investors' investment decisions. The research results show that overconfidence and loss aversion bias positively and significantly influence investment decisions. Apart from that, the results also show that robo-advisors succeed in weakening the relationship between overconfidence bias and investment decisions. Meanwhile, robo-advisors show results that cannot moderate the relationship between loss aversion and investment decisions. Keywords: Robo-advisor, behavioral bias, overconfidence, loss aversion, mutual fund investment decision